The Relationship Between Attention Control and Grammatical Processing - Sari Harahap, Indah Permata; Lubis, Elfi Mawaddah; Lubis, Nurul Hidayah; Lubis, Yani (MUDABBIR Journal Research and Education Studies, 2025)
This study investigates the relationship between attention control and grammatical processing, focusing on how cognitive regulation contributes to learners’ ability to comprehend and produce grammatically accurate language structures. As attention control is essential for managing competing linguistic information, individuals with higher attentional regulation are expected to demonstrate more effective processing of complex grammatical cues. Using an experimental design, participants completed a set of attention control tasks alongside grammar judgment and sentence-construction assessments. The findings reveal that attention control significantly predicts grammatical accuracy, suggesting that learners with stronger cognitive focus are better equipped to detect grammatical violations, allocate mental resources efficiently, and maintain working memory performance during linguistic tasks. Additionally, the results highlight the mediating role of selective attention in parsing syntactic structures, particularly in conditions involving distractors or increased cognitive load. This study contributes to psycholinguistic research by emphasizing the interplay between cognitive control mechanisms and linguistic competence. It also offers pedagogical implications, indicating that instructional strategies aimed at improving attention regulation may enhance grammar learning outcomes. Future research is encouraged to explore longitudinal patterns of this relationship and examine how attention-training interventions may strengthen grammatical proficiency across diverse learner populations.